Efficient load sharing scheme for large distributed systems - Sheeja Mohan. (2011)
The availability of low-cost computers and advances in communication technologies have spurred considerable interest in distributed systems that consists of a collection of autonomous computers (nodes) interconnected by a network. However, to make full use of the enormous computing power available in the system, it is necessary that the resources be utilized effectively. Load sharing is a key technique employed to effect better resource utilization as it improves the performance of the system by "smoothing out" the periods of high congestion at individual nodes. The congestion at a node is due to the random nature of the task arriving at each node of the system for the service.